CRIMINAL POLICY IN CHILDREN'S CONSTRUCTION EFFORTS AS A NARCOTIC CRIMINAL ACTION PERSON - Frans Simangunsong (UNTAG Law Review, 2018)
Cases of narcotics abuse are increasing. This is evidenced by the almostdaily press reports from newspapers and electronic media about smuggling, illegaltrade, arrests and detention related to the problem of narcotics abuse. The purpose ofnarcotics abuse is a deviant or accidental use of narcotics. So the act violates the law andis threatened with criminality. Criminal policy in an effort to control children asperpetrators of narcotics crimes. Threats of imprisonment that can be imposed onchildren no later than 1/2 (one half) from the maximum threat of imprisonment foradults. This means that the criminal threat for children who become narcotics couriers ishalf of the criminal threats contained in the Narcotics Law. For children who becomecouriers or narcotics brokers, they must be based on the mechanism stipulated in theChild Protection Act and the Juvenile Justice System Law. Law enforcement forperpetrators who are still under age, there is a special provision called diversion, namelythe transfer of settlement of child cases from criminal justice processes to processesoutside of criminal justice